New marketing in fashion e-commerce. Issue 1 (2nd January 2018) - Guercini, Simone; Bernal, Pedro Mir; Prentice, Catherine
Abstract: This paper introduces a special issue devoted to the emergence of new marketing models and tools within a fashion e-commerce context. Despite the importance of physical stores, in recent years, we have witnessed substantial development regarding the electronic trade in fashion products. In effect, fashion products represent a major category within e-commerce and have witnessed the development of a "new" form of online marketing. Special attention should be paid to the internationalization of e-commerce within the fashion industry. New models and tools have emerged in relation to: the technology/consumption interface and the strategies of the different players within the business sector; the integration of online and offline fashion marketing; the impact of new IT technologies and new marketing on preexisting fashion marketing policies, such as customization; and the role of new emerging players such as fashion bloggers and influencers. In this period of change, new and traditional marketing tools co-exist. The five articles in this special issue seek to contribute to research whose aim is to systemize new models and tools that may be useful for practitioners and marketing researchers working in this field.